Philo of Alexandria on the contents of the Book of Genesis (Abr. 1) - B. M. Nikolsky (Шаги)
The article discusses the strange presentation at the beginning of Philo of Alexandria’s On Abraham of the main content of the Book of Genesis as an account “of fruitfulness and barrenness, of dearth and plenty; how fire and water wrought great destruction of what is on earth; how on the other hand plants and animals were born and throve through the kindly tempering of the air and the yearly seasons.” The Book of Genesis is not a natural science treatise or a history of meteorological and climatic phenomena. Why then does Philo give it such a strange characterization? Philo’s words are correlated with topoi common in the philosophical literature of his time, and the following explanation is offered. Philo relates his main idea, the idea of the correspondence of human law to natural law, in both of which the virtues of humanity and justice are equally manifested, to the plan of the Book of Genesis. He wants to present it as an account first of the law of the world, then of human laws. The laws of nature are to be presented in the account of the creation of the world. But the actual content of the beginning of the Book of Genesis differs from what Philo expects from it; the reasoning he needs about humanity and justice present in God’s created world is not there. Philo finds it not in the creation of the world, but in its existence, not in the opening chapters, but in the continuation of the Book of Genesis. However, here, in this part of Genesis, the natural world has no independent significance; this part is already devoted to human life. Thus, it turns out that topics that have only indirect significance in the Book of Genesis itself, unexpectedly become for Philo important themes of the Pentateuch in their own right.